Loneliness, Number of Facebook Friends, and Facebook Addiction among University Students - Naher, Lutfun; Hossain, Muhammad Alamgir; Ahmed, Oli (Chittagong University Journal of Biological Sciences, 2024)
Facebook addiction gets huge attention among researchers as a new form of behavioral addiction. The present study aimed to assess the role of loneliness and the number of friends on Facebook as risk factors of Facebook addiction. Necessary information was collected from a sample of 234 students who were selected through non-probability sampling techniques using a structured questionnaire that contained the UCLA Loneliness scale, Bergen Facebook addiction scale, questions regarding the number of Facebook friends and personal information. Results showed male Facebook users had higher number of Facebook friends than female users. Results also explored that loneliness, the number of Facebook friends, and being female were significant predictors of Facebook addiction. These findings would help respective authorities take proper initiative for reducing loneliness and Facebook addiction and ensuring sound mental health for making students as future leaders of the country's development. The Chittagong Univ. J. B. Sci.,Vol. 10(1 &2):139-148, 2020